1999
DOI: 10.1071/a98075
|View full text |Cite
|
Sign up to set email alerts
|

Potential for selection to improve efficiency of feed use in beef cattle: a review

Abstract: Evidence for genetic variation in feed efficiency of beef cattle is reviewed in this paper, and ways in which this variation might be used in selection programs to improve beef cattle in Australia are discussed. Efficiency of beef production systems is determined by feed and other inputs of all classes of animals in the production system as well as outputs in terms of slaughter progeny and cull cows. Different indices have been used to express aspects of efficiency on cattle over certain periods of the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
201
2
50

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 310 publications
(263 citation statements)
references
References 0 publications
10
201
2
50
Order By: Relevance
“…Results of this study are in agreement with those of Archer et al (1999) and Arthur et al (2001b) that genetic variation exists among individual animals for RFI. On average, high RFI P bulls consumed 17.3% more feed than low RFI P bulls, a value that agrees very well with the 18% difference in the Brangus heifer data analyzed by Lancaster et al (2009).…”
Section: Discussionsupporting
confidence: 93%
“…Results of this study are in agreement with those of Archer et al (1999) and Arthur et al (2001b) that genetic variation exists among individual animals for RFI. On average, high RFI P bulls consumed 17.3% more feed than low RFI P bulls, a value that agrees very well with the 18% difference in the Brangus heifer data analyzed by Lancaster et al (2009).…”
Section: Discussionsupporting
confidence: 93%
“…The literature generally agrees that genetic variation in feed efficiency exists (review by Archer et al 1999). These variations in feed efficiency potentially represent an opportunity for beef producers to significantly reduce production costs by reducing feed intake while maintaining growth rate.…”
Section: Introductionmentioning
confidence: 90%
“…A review by concluded that differences in efficiency of maintenance exist between breeds, and these differences are correlated with differences in productive potential of breeds. Efficiency of feed utilisation has several variable components including feed intake, digestion of feed, metabolism (including variation in body composition), activity and thermoregulation (reviews by Archer et al 1999;Herd et al 2004). Early research on tropically adapted genotypes (Vercoe 1967(Vercoe , 1970Vercoe 1969, 1977;Vercoe et al 1972) shows there are differences in feed intake, eating rate, weight gain, metabolic rate and efficiency of feed utilisation between breeds and across different environments.…”
Section: Introductionmentioning
confidence: 99%
“…The lower RFI suggests a greater efficiency of feed use for BRAH for the same MWT and TADG, which is in contrast with the higher observed feed conversion ratio for BRAH. RFI and feed conversion ratio are quite different traits (Archer et al 1999); Robinson and Oddy (2004) and Arthur et al (2001) found the correlation to be 0.66 in Angus. In the feed conversion ratio trait, there is no consideration of the feed required to maintain liveweight.…”
Section: Mean Performance Of Brahman and Tropical Compositementioning
confidence: 99%
“…on genetic and phenotypic correlations, variances and means for live steer production traits including, as a particular focus, individual daily (DFI) and residual (RFI) feed intake. RFI is a measure of the efficiency of feed use that is being actively researched for use in genetic evaluation (Archer et al 1999;Arthur et al 2004;Herd et al 2003). A further aim was to evaluate the potential of measures, including insulin-like growth factor-I concentration (IGF-I), as genetic indicators of RFI.…”
Section: Introductionmentioning
confidence: 99%